16th International Conference on Evaluation &Amp; Assessment in Software Engineering (EASE 2012) 2012
DOI: 10.1049/ic.2012.0031
|View full text |Cite
|
Sign up to set email alerts
|

Risks of off-the-shelf-based software acquisition and development: a systematic mapping study and a survey

Abstract: Background Risks associated with a software project have the potential to affect all stakeholders. Today much software makes use of off-the-shelf (OTS) components. A better understanding of OTS-derived software risks will help to define responsibilities for these risks, and also to avoid them. Aim Our objective is to identify, classify and compare risks of OTS-based software projects from both a software development and a software acquisition perspective. Method To identify and classify the risks, we performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 7 publications
0
17
0
Order By: Relevance
“…This mapping study identifies the risks a give a checklist of the risks. COTS study [11] . COTS integration [12] is a process which plays a vital role.…”
Section: Related Workmentioning
confidence: 99%
“…This mapping study identifies the risks a give a checklist of the risks. COTS study [11] . COTS integration [12] is a process which plays a vital role.…”
Section: Related Workmentioning
confidence: 99%
“…The study showed that system integrators consider architectural knowledge valuable to assess the architectural fit of the component and understand how the component can be used for a CBS. Kusumo et al [31] reported the results of a mapping study of published papers on risks associated with off-the-shelf component-based software development. They classified off-the-shelf-based development risks into 17 categories ranging from planning risks to legal risks.…”
Section: Component Integration Challenges and Empirical Evaluationmentioning
confidence: 99%
“…However, to the best of our knowledge, none of the existing work presents an industrial study to investigate the impact of integration process activities during the development of a CBS. [9,23,31] specify individual component quality properties. 'structural compatibility analysis' [6,13,14,28,31] analysing component interfaces to deal with potential mismatches between components.…”
Section: Component Integration Challenges and Empirical Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…Software acquisition is considered a risky and complex activity [6]. According to results published in [7], risks occurred more frequently in software acquisition than in software development. Decision has also to consider "good enough" solutions, because the high number of criteria and most often the shortage of time makes it difficult to choose the best solution.…”
Section: Introductionmentioning
confidence: 99%